2022
DOI: 10.1186/s12964-022-00876-6
|View full text |Cite|
|
Sign up to set email alerts
|

Follicular fluid-derived exosomal miR-143-3p/miR-155-5p regulate follicular dysplasia by modulating glycolysis in granulosa cells in polycystic ovary syndrome

Abstract: Objective Polycystic ovary syndrome (PCOS) is characterized by follicular dysplasia. An insufficient glycolysis-derived energy supply of granulosa cells (GCs) is an important cause of follicular dysplasia in PCOS. Follicular fluid (FF) exosomal microRNAs (miRNAs) have been proven to regulate the function of GCs. In this study, exosomes extracted from clinical FF samples were used for transcriptome sequencing (RNA-seq) analysis, and a human ovarian granulocyte tumour cell line (KGN cells) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an omission in the Funding section. The funding section should read as follows:…”
Section: Correction To: Cell Communication and Signaling(2022)20:61 1...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified an omission in the Funding section. The funding section should read as follows:…”
Section: Correction To: Cell Communication and Signaling(2022)20:61 1...mentioning
confidence: 99%
“…Author details 1 Guangxi Key Laboratory of Environmental Exposomics and Entire Lifecycle Health, Guilin Medical University, Guilin 541199, China.…”
Section: Publisher's Notementioning
confidence: 99%
“…8 Several studies reported many differentially expressed miRNAs in exosomes of follicular fluid of PCOS women, which can promote granulosa cell apoptosis and follicular dysplasia. [9][10][11][12] PCOS, as a systemic disease, compromises many organs, not merely the ovaries. Che X et al found miR-27a-5p in serum exosomes was upregulated and affected TGF-β signaling pathways leading to increased risk of endometrial cancer in PCOS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed to investigate the functional changes of CCs in EM-associated infertility patients, however, it is di cult to obtain primary human CCs in a sizable amount and culture many generations in vitro. Human granulosa-like tumor cell line KGN maintains the physiological characteristics of normal GCs and well grows many times of passages in culture (12), and KGN cells have been extensively used to study the function and regulatory mechanism of biological factors of GCs (13)(14)(15). Therefore, KGN cells were used for further functional and mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%